Obraz powstań śląskich w wybranych utworach niemieckich pisarzy (PDF 1,40 MB) (Książnica Śląska, 2025)
The Plebiscite and the Silesian Uprisings ware a frequent topic inGerman literature, which in 1920’s resulted in forming a genre called Grenzlandroman (frontier novel). With specific examples the author presents various interpretations of events of the years 1919–1921from German citizens’ point of view. Some writers tend to idealizeGermans’ demeanour and express their dislike for Poles. However,there are also some who deeply believe in harmonious coexistence ofthe two feuding nations or even express admiration for the Polish politician Wojciech Korfanty.